2005
DOI: 10.1590/s0100-72032005000600008
|View full text |Cite
|
Sign up to set email alerts
|

Comparação da linfocintilografia com dextrano 500 com a do fitato na pesquisa do linfonodo sentinela no câncer de mama

Abstract: Objetivo: comparar a acurácia de dois radiocolóides na marcação do linfonodo sentinela (LNS) por imagem. Métodos: as pacientes foram incluídas no período de maio de 2002 a abril de 2004. Neste estudo duplo-cego, a paciente foi submetida duas vezes ao mesmo exame, mas com fármacos diferentes, sendo que os fármacos, tecnécio-99m-dextrano 500 (dextrano) e tecnécio-99m-fitato (fitato), foram injetados, na mama, em quatro pontos na área peritumoral e no subcutâneo superficialmente ao tumor, com volume de 2 mL, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Technetium-99m is widely used and marked with radiocolloids, with dextran 500 being the most appropriate colloid due to its good performance and ideal particle size. 28 Before the present study, it was believed that, during the early postoperative period, superficial infraumbilical lymphatic drainage occurred toward the axillary lymph nodes in all cases. This was the prevailing opinion, because after abdominoplasty, infraumbilical tissue originated in the supraumbilical region.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Technetium-99m is widely used and marked with radiocolloids, with dextran 500 being the most appropriate colloid due to its good performance and ideal particle size. 28 Before the present study, it was believed that, during the early postoperative period, superficial infraumbilical lymphatic drainage occurred toward the axillary lymph nodes in all cases. This was the prevailing opinion, because after abdominoplasty, infraumbilical tissue originated in the supraumbilical region.…”
Section: Discussionmentioning
confidence: 69%
“…Technetium-99m is widely used and marked with radiocolloids, with dextran 500 being the most appropriate colloid due to its good performance and ideal particle size. 28…”
Section: Discussionmentioning
confidence: 99%
“…However, in 33.3% (3/9), no SLN was ever seen and these patients, then, underwent AL. In these three cases, the exam with HE ascertained that 71.9% (46/64) of the dissected lymph nodes were involved with tumor (Table 1) Urban et al (2001) and Xavier et al (2005) found that advanced age can contribute to radiopharmaceutical failure in identifying the SLN, possibly due to liposubstitution of the lymphoid tissue. Birdwell et al, (2001) suggested that lower rates of SLN identification related to age were due to decreased breast tissue turgor in older women, resulting in lower hydrostatic pressure in the lymphatic channels and lower impulsion power of the radiocolloid, besides the decreased phagocytic function of the lymph node itself, which in older women shows reduction of the sinusoidal spaces due to liposubstitution.…”
Section: Resultsmentioning
confidence: 95%